Superstar Salaries and Soccer Success: The Impact of Designated Players in Major League Soccer. (October 2016) - Coates, Dennis; Frick, Bernd; Jewell, Todd
This study estimates the relationship between production and salary structure in Major League Soccer (MLS), the highest level of professional soccer (association football) in North America. Soccer production, measured as league points per game, is modeled as a function of a team's total wage bill, the distribution of the team's wage bill, and goals per game. Both the Gini coefficient and the coefficient of variation are utilized to measure salary inequality. The results indicate that production in MLS is negatively responsive to increases in the salary inequality; the estimation model with the best fit uses the coefficient of variation to measure dispersion. Furthermore, MLS teams appear to be constrained in their choices of salary inequality by the salary cap and other regulations.